Jornalismo, literatura e cinema: o romance-reportagem de Aguinaldo Silva e sua adaptação cinematográfica - Dias, Mariane Bovoloni [UNESP] (2015)
This dissertation focuses on the problem of the adaptation of the literacy text to audiovisual media, based on the book Lili Carabina: An obsession Portrayal, wrote by Aguinaldo Silva in 1988. Ar the same year, the novel-report was adapted to the movie Lili, Notorious Criminal, directed by Lui Farias. We are interested about the union between literature and the cinema, and the elements of adaptation. This analysis try to understand the aspects that characterize the process of literacy adaptation for audiovisual